Effects of an early transfer from incubator to a warming crib in very low birthweight preterm infants - Sandra Greve; Nora Bruns; Anne-Kathrin Dathe; Michael M. Schuendeln; Ursula Felderhoff-Mueser; Anja Stein (BMC, 2024)
Abstract Purpose Very low birth weight infants are cared for postnatally in the incubator because of adverse consequences of hypothermia. Data on the optimal weight of transfer to a warming crib are rare. The aim of this study was to determine the course of temperature and body weight during a standardized transfer to a warming crib at a set weight. Methods Prospective intervention study in very low birthweight infants who were transferred from the incubator to a warming crib at a current weight between 1500 g and 1650 g. Results No infant had to be transferred back to an incubator. Length of hospital stay was equal compared to a historical cohort from the two years directly before the intervention. The intervention group showed an increase in the volume fed orally on the day after transfer to the warming crib, although this did not translate into an earlier discontinuation of gavage feedings. Compared to the historical group, infants in the intervention group could be transferred to an unheated crib at an earlier postmenstrual age and weight. Conclusions Early transfer from the incubator to a warming crib between 1500 g and 1650 g is feasible and not associated with adverse short-term events or outcomes. Trial registration DRKS-IDDRKS00031832.